(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study examines the dynamics of power and authority in high school principal leadership, emphasizing the impact of power utilization, leadership styles, and organizational political processes on the efficacy of educational management. The research was executed via a literature review, analyzing books, scientific journals, government regulations, and diverse literature pertinent to educational leadership. The research findings indicate that the principal’s power is not solely derived from structural legitimacy, but also from expertise, social connections, integrity, and interpersonal skills, which have been proven to enhance moral authority. For a school to have a good, collaborative, and quality-oriented climate, there needs to be a balance between formal power and professional authority. The ethical use of power and authority includes transparency, fairness, accountability, and a student-centered approach, which are key to reducing resistance, increasing trust, and strengthening school culture. This research substantiates that the efficacy of school principal leadership directly influences the quality of learning, organizational culture, and the success of educational transformation